Pengaruh ZIS Dan Faktor Makro Ekonomi Terhadap Tingkat Kemiskinan Di Indonesia - Ira Humaira Hany; Dina Islamiyati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
Poverty in a country must be dealt with in order for the country to develop better. One of the indicators to say a country is well-developed is when the poverty level in that country is low. So a solution is needed to overcome poverty. One of the objectives of this research is to find out the influence of the distribution of Zakah, Infaq, and Shodaqoh (ZIS) of the National Amil Zakat Council, Inflation and Economic Growth on Poverty Rate in Indonesia for the period 2006-2018. This research uses quantitative methods with multiple linear regression analysis. Endogenous variables are poverty levels, while exogenous variables are the distribution of ZIS funds, inflation, and economic growth. The data used are secondary data from BAZNAS and BPS. ZIS partially has a significant influence on poverty levels based on the T-Test. The F-test shows that all variables simultaneously have a significant influence on poverty in Indonesia in the period of 2006-2018.